Surface Acoustic Wave Interaction with a Mixture of Oxygen and Nitrogen - PASTERNAK, Mateusz; JASEK, Krzysztof; GRABKA, Michał; BOROWSKI, Tomasz (Archives of Acoustics, 2020)
Parameters of surface acoustic waves (SAW) are very sensible to change of physical conditions of a propagation medium. In the classical theory formulation, the waves are guided along the boundary of semi-infinity solid state and free space. A real situation is more complex and a medium commonly consists of two physical components: a solid substrate and a gaseous or liquid environment. In the case of stress-free substrate, the strongest impact on SAW properties have surface electrical and mechanical conditions determined by solids or liquids adhering to the boundary. This impact is utilised for constructing sensors for different gases and vapours e.g. (Jakubik et al., 2007; Hejczyk et al., 2011; Jasek et al., 2012). The influence of gaseous environment on the SAW properties is usually very weak and ignored. However, in certain condition it can be significant enough to be applied to sensor construction. In general, it concerns Rayleigh wave devices where energy leakage phenomenon is perceptible, especially when the gas being detected considerably changes the density of environment. The paper presents the results of experiments with oxygen-nitrogen mixture. Their primary aim was focused on finding the dependence of resonant frequency and attenuation in SAW resonator on parameters and concentrations of the gas in the environment.